UiTM (Perlis) web-based of Al-Farabi 3 : ICT devices Inventory / Nur Anis Sofea Zulkiflee - Zulkiflee, Nur Anis Sofea (2020)
Presently, facility management is a growing for both academic studies and construction. Responsibility for wide range of services such as utilities generation, operation and maintenance, construction, and distribution are being taken by facilities management departments in most agencies. They responsible to involve query, edit and update data for emergency response and other important tasks which is regarding to facilities. However, there is no system involve the time consuming for maintenance. The aim of this study to develop a GIS web-based system on facility management in Al-Farabi 3. To achieve the aim, the objectives of this study are: 1.to display ICT inventory through web site platform and 2. to implement and testing the performance of the web-based system. In this study, several data is used such as spatial data and attribute data using Arcmap software covered area Universiti Teknologi Mara (UiTM) Arau, Perlis. In ArcMap, spatial entities were extracted from the digitized by either importing them to the geodatabase. Example of attribute data required is building name, room name and ICT devices. The significant of this study is able to access through the website platform to monitor ICT devices inventory.